Transverse Beam Profile Analysis of a Plasma Sputter Ion Source - Mendenilla, Alexander; Blanca, Carlo Mar; Ramos, Henry (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The beam profile of an existing plasma-sputter-type negative ion source with a titanium target is analyzed. The transverse characteristics of the ion beam are investigated and the deposition capability of the system is characterized. The ambient plasma parameters are derived via a Langmuir probe indicating an electronic density of 9.2 x 10 10 cm -3 and temperature of 2.14 x 10 4 K near the center of the ion beam. Simulated negative ion distributions show that the energy content of the deposition plasma is three orders of magnitude lower than the expected current amplitude-the apparent effect of beam defocus. Although attenuation of the incident beam is apparent, the beam is basically monoenergetic, with a maximum energy spread of 8eV.